Analyzing the kinetics in the filtration drying of crushed cotton stalks - Kobeyeva, Zagira; Khussanov, Alisher; Atamanyuk, Volodymyr; Hnativ, Zoriana; Kaldybayeva, Botagoz; Janabayev, Dauren; Gnylianska, Lesia (Eastern-European Journal of Enterprise Technologies, 2022)
The drying of crushed plant-derived materials, in particular crushed cotton stems, is a complex heat-exchange and technological task. Resolving this task successfully ultimately determines the specific energy costs of the drying process and the quality of the resulting products. The rational drying regime of crushed cotton stems should ensure the minimum possible process duration, energy costs, and provide the necessary quality characteristics of the dried material. To address this issue, it is necessary to investigate the influence of technological parameters of the process (the temperature and filtration rate of the heat agent), as well as the thickness of the stationary layer of crushed cotton stems, on drying kinetics. This paper has generalized experimental studies into the kinetics of filtration drying of crushed cotton stems during the period of complete saturation of the thermal agent with moisture. The influence of the temperature of the drying agent, the speed of its filtering through a stationary layer of different heights of wet crushed cotton stems, on the kinetics of filtration drying has been shown. The study's results demonstrate the dynamics of moisture removal at different parameters of the heat agent and the heights of the stationary layer of crushed cotton stems. The resulting dependence has been established, which is used to determine the value of the kinetic coefficient η for crushed cotton stems; the value of the kinetic coefficient has been calculated, a=20.74 1⁄m. The dependence has been derived, using which makes it possible to generalize the kinetics of filtration drying of crushed cotton stems during the period of complete saturation of the heat agent with moisture within the limits of changing the moisture content of the veneer The comparison of the experimental data with those obtained theoretically has shown that the maximum absolute value of relative error does not exceed 15.2 %.